Aciepe Children's Stories and Mathematics: an educational instance - Ana Paula Gestoso de Souza; Rosa Maria Moraes Anunciato de Oliveira (Universidade Federal do Rio Grande do Sul, 2014)
This paper analyzes the dynamics of the Curricular Activity of Teaching, Research, and Extension Integration (Aciepe), called Children's Stories and Mathematics in the Elementary School, based on the trajectory of Pedagogy graduates. We chose the case study of ACIEPE, based on the account of its five participants. We analyzed multiple data sources - written records produced over this research, interviews, and questionnaires answered after the end of the activity. The results show the constitution of Aciepe as an educational instance that promotes the teacher's professional development and learning, supported by the institution.